Detection of herpes simplex type 2 in indian women state Zulia - Ana Luzardo; Luciana Costa de León; Francisca Monsalve; María Castellanos; Yenddy Carrero S.; Rita Fernández F; Ricardo Atencio T. (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
The herpes simplex virus type 2 (HSV-2) is a sexually transmitted infection prevalent in the world; in spite of despite diagnostic and therapeutic advances. According to estimates in 2012, it was calculated that there were 417 million people infected worldwide. The objective of this project was to detect HSV-2 in indigenous women of the Zulia state, for that 100 women of the Wayúu and Añú ethnic groups, were selected without discriminating age and/or parity. The physician proceeded to sample with an alginate swab, for the processing of the same was used the polymerase chain reaction (PCR) method to detect HSV-2 in samples of cervical-uterine origin, and cytological diagnosis was made through staining with hematoxylin-eosin. 22% of HSV-2 positive samples were obtained, the results show that a considerable percentage of patients present HSV-2 infection, which is extremely important because it can contribute to the progression of processes inflammatory agents.